Travels broaden the mind - Netyazhevskyy, Alexander (My University, 2014)
Our world is a great mixture of places, people, things, built by humans, or other, created by nature. It is like a huge whirlpool, twirling you in its deep layers of knowledge.
Keywords: культура; традиції; подорожі; пізнання; традиции; путешествия; изучение; cultures; traditions; travelling; learning; кафедра іноземних мов професійного спрямування